Evaluation and impact assessment of culture‐based fisheries to enhance fish yield in small reservoirs in Odisha State, India. (15th May 2020) - Sarkar, Uttam K.; Lianthuamluaia, Lianthuamluaia; Panda, Debabrata; Kumari, Suman; Parida, Pranaya K.; Karnatak, Gunjan; Mishal, Puthiyottil
Abstract: The present study investigates the success of stocking fingerlings of Indian major carps ‐ Gibelion catla (Hamilton), Labeo rohita Hamilton and Cirrhinus mrigala Hamilton – to enhance fish yield in 58 small reservoirs in Odisha State, India. Fish stocking and yield data were collected from State Fisheries Department, Odisha. The relationships between area, stocking density and fish yield of different size groups of reservoirs were assessed using the Pearson correlation coefficient ( r ). Fish yield increased significantly ( p  < 0.05, t ‐test) from 204 kg/ha/year in 2012–13 to 323 kg/ha/year in 2013–14 due to adoption of CBF. The corresponding per capita fish production increased from 398 kg fisher −1 year −1 to 702 kg fisher −1  year −1 benefitting more than 8, 000 fisher households. Reservoirs in the size group 100–500 ha showed the highest response of fish yield with respect to stocking of fingerlings. The size of fingerlings at stocking and area of the reservoir had greater impact on enhancing fish yield. Stocking had a profound positive impact on fish yield. This study forms a baseline evaluation of the impact of stocking on small tropical reservoirs in India. It also recommends management measures and discusses issues, and the way forward for sustainable fisheries enhancement in small tropical reservoirs in eastern India.